Reverse time migration based on local Nyquist cross-correlation imaging condition with accurate first-arrival traveltimes correction - LiJun, Gao; ZongJie, Li; HaiYing, Li; Wei, Yang; Qing, Zhang (Frontiers in Earth Science, 2025)
The selection of imaging conditions is one of the most critical factors determining the quality of reverse time migration (RTM) images. Among the widely used imaging conditions, the cross-correlation imaging condition (CCIC) consistently delivers high-resolution images. However, it is accompanied by substantial calculational costs and I/O tasks, particularly in 3D scenarios. In contrast, the excitation amplitude imaging condition (EAIC) offers advantages in computational efficiency, low storage requirements, and high precision. Nevertheless, it suffers from image distortion when dealing with multi-path propagation or strong reflection interfaces. The local Nyquist cross-correlation imaging condition (LNCIC) effectively combines the advantages of the two aforementioned imaging conditions. It uses the local wavefield near the time corresponding to the maximum amplitude at each grid point for imaging, and introduces the Nyquist sampling theorem to establish the search time step. This approach offers the benefit of high imaging quality while maintaining low storage cost. In this paper, we adopt an adaptive finite difference operator to solve the eikonal equation and calculate the accurate first-arrival traveltimes, thereby modify LNCIC and further enhancing the imaging accuracy. The effectiveness of the proposed method is demonstrated through numerical examples, including the Marmousi model, noise-resistance tests, and field data applications.